The Socialization of Health Protocols During the Covid – 19 Pandemic Taklim Council of Sri Rahayu Village - Apri Budianto; Diny Vellyana (Perkumpulan Peneliti Ilmu Lingkungan - Green Visioneers, 2021)
Since mid- May New Normal has been implemented in the Pringsewu area of Lampung, however New normal can be an opportunity for virus transmission if it is carried out without considering the New Normal health protocol recommended by the Indonesian government through the Indonesian Ministry of Health. This become more alert when it was reported that the increase in the status of Covid – 19 pandemics in Pringsewu Regency on January 19, 2021 become red zone. Including in the Sri Rahayu Village with the active social activity. Based on these conditions, special attention is needed in carrying out the New Normal, through this community service, it aims to minimize the risk of contracting Covid – 19 through socialization of health protocols for the implementation of the New Normal in the Community. The method used was using demonstration and explanation with power point and protocol equipment. All of the participant of this community dedication.